The Effect of Providing Education Through Video on the Level of Knowledge of Inhaler Use in Asthma Patients - Hamdani, Ade Sukma; Anggita Putri, Zahwa (THRIVE Health Science Journal, 2025)
Asthma is a heterogeneous lung disease that affects more than 300 million people. The most ideal dosage form for asthma therapy is via the inhalation route, namely with a device called an inhaler. This study aims to see the effect of providing education via video to outpatient asthma patients at the Praya Regional Hospital, Central Lombok, NTB Province. The Wilcoxon test was carried out to determine the significance of changes in knowledge and attitudes about asthma prevention before and after treatment at the 95% confidence level (ɑ=0.05). From the research results, it is known that 61.54% of the 13 respondents from asthma outpatients at Praya Regional Hospital were men, and 38.46% were women and were dominated by people aged >45 years. Patients admitted that their asthma complaints were caused by a history of allergies, as many as 61.54% were allergic to dust, followed by allergies to cold and food (seafood). The number of samples was limited so a chi-square test was carried out which then found a relationship between two variables, namely gender and length of inhaler use with the knowledge score on how to use the inhaler correctly which was marked with a significance value. <0.05.